STUDI PREVALENSI RISIKO DIABETES MELITUS PADA REMAJA USIA 15–20 TAHUN DI KABUPATEN SIDOARJO - Andini, Ary; Awwalia, Evy Sylvia (Jurnal Ilmu Kesehatan dan Kesehatan, 2018)
Abstract: Worldwide number of adolescents diagnosed with diabetes mellitus has increased everyyear means that a prevention to reduce the prevalence of diabetes mellitus is required. The aim ofthis study was to determine the prevalence of diabetes mellitus risk in adolescents in Sidoarjo city,East Java and Diabetes Mellitus risk factors. Total population used in this study is composed by 150men and women aged 15–20 years who reside in various locations in Sidoarjo city. The obtaineddata were analyzed descriptively with cross-sectional design. The results showed the prevalence ofdiabetes risk in adolescents in Sidoarjo is about 42% with average glucose levels 104.35 ± 13.01mg/dl. The prevalence of non-diabetes mellitus in adolescents is 58% with the average glucose79.26 ± 7.01 mg/dl. The risk factor which lead to high risk of diabetes mellitus is fast-food consumption (71%), soft drink consumption (31%) and smoking (5%).